Sustained release of tea polyphenols from a debranched corn starch–xanthan gum complex carrier. (April 2019) - Hong, Yan; Yang, Jie; Liu, Wei; Gu, Zhengbiao; Li, Zhaofeng; Cheng, Li; Li, Caiming; Duan, Xuejun
Abstract: Tea polyphenols (TPP) are natural antioxidants that have many beneficial physiological effects. However, the low oral bioavailability of TPP has led to attempts at their encapsulation for sustained release. In this study, to obtain an adequate complex carrier for TPP, debranched corn starch (DBCS) with different relative debranching degrees were prepared by controlling hydrolysis time and enzyme concentration. This study aimed to obtain TPP-loaded DBCS-xanthan gum-based microcapsules using spray-drying for the sustained release of TPP to improve its bioavailability and half-life. The strong gel network structure of the wall material caused to the more compact and viscous complex carrier observed by scanning electron microscopy, which was beneficial for the slow release of TPP from the microcapsule. The increased amylose content, decreased relative molecular weight and molecule size may contribute to the anti-digestibility of the wall material when NCS was debranched moderately, which was beneficial for the slow release of TPP. The in vitro release results demonstrated that DBCS with a 34% relative debranching degree exhibited 30% and 80% release in simulated gastric and intestinal fluids, respectively. Highlights: Tea polyphenols are antioxidants with beneficial effects but low oral bioavailability. Debranched corn starch with xanthan gum was used as carrier for sustained release. Microcapsules with 34% debranching degree presented suitable preparation performance.